Experiences of caring for Boyaca women submitted to mastectomy by cancer de seno - Marianne Arlette Durán Avendaño; Carmen Helena Ruiz de Cárdenas (Universidad de Alicante, 2019)
Objective: To describe the core experiences of Boyaca women, undergoing mastectomy for breast cancer, during 2017. Methodology: Qualitative ethnographic type according to the small-scale ethno-nursing, of Leininger's transcultural theory. The participants included ten women key informants and eight general informants. The analysis of the information obtained in the interviews was developed in four phases: 1. Collection, description and documentation of raw data; 2. Identification and categorization of the descriptors and components; 3. Contextual and pattern analysis; 4. Central themes, research findings, theoretical formulations, and recommendations. The analysis was made taking into account the guide proposed by Leininger. The factors of the social and cultural structure, of the model of the rising Sun The experiences of care experienced by women were described identifying a total of two hundred and eight codes and twenty recurring patterns, which were analyzed and according to the level of coding were labeled and coded giving rise to six themes: 1. The accompaniment an important part in the care of the woman subjected to Mastectomy; 2. The strength of faith; 3. Unpleasant effects of treatment; 4. Experience lived; 5. Importance of care in recovery; 6. Feeding basic support in recovery.